Youth Participation in Agricultural Cooperatives, Post Covid-19 Strategies: A Case of Machakos Coffee Co-operative Societies, Kenya - Ngala, Orucho Michael (Archives of Business Research, 2022)
Kenya is a country that is mainly dependent on the agriculture sector for livelihood. Smallholder farmers through Coffee Cooperative Societies play a central role in socio-economic development, particularly in agricultural production, processing, and marketing. The vibrant and dynamic cooperative movement enhances food security, wealth creation, and poverty eradication. FAO report indicates that youths in Kenya are a critical component of the productive population and their input can be harnessed to enhance economic development. However, Kenyan youth has not actively embraced agriculture, due to the involvement of manual labour and poor returns. This study sought to establish factors affecting youth participation in coffee cooperative societies in Machakos County, Kenya. Eighty (80) youth from the eight (8) coffee cooperative societies working under Sustainability Kenya Limited Networks -AGRIFI Project in Machakos County were involved in the study. Focus group discussion (FGD) was adopted to gather in-depth data. Older men’s domineering culture, lack of succession planning, resource allocation challenges, and a negative attitude that associates agriculture with the elderly, the poor, the illiterate, and rural folks, were identified as the main factors impeding active participation of the youth in coffee cooperative societies. The study observes that covid-19 has shaken the whole world, setting in motion unavoidable waves of change, with a wide range of uncertain trajectories in the future. The whole world has moved drastically toward online channels to cope with pandemic challenges. The study strongly recommends deliberate attempts to incorporate technology into agriculture as a strategy of motivating the youth to engage in agriculture and associated cooperatives, thereby increasing agricultural production. Young people easily embrace new ideas, experiment with new practices, and are often devoid of technophobia. They are a potential vital force for innovation in cooperative societies and can contribute immensely to the well-being of farmers, families, and to the local communities.